Size and Carbon Content of Sub-seafloor Microbial Cells at Landsort Deep, Baltic Sea - Braun, Stefan; Morono, Yuki; Littmann, Sten; Kuypers, Marcel; Aslan, Hüsnü; Dong, Mingdong; Jørgensen, Bo B.; Lomstein, Bente Aa. (Frontiers in Microbiology, 2016)
The discovery of a microbial ecosystem in ocean sediments has evoked interest in life under extreme energy limitation and its role in global element cycling. However, fundamental parameters such as the size and the amount of biomass of sub-seafloor microbial cells are poorly constrained. Here we determined the volume and the carbon content of microbial cells from a marine sediment drill core retrieved by the Integrated Ocean Drilling Program (IODP), Expedition 347, at Landsort Deep, Baltic Sea. To determine their shape and volume, cells were separated from the sediment matrix by multi-layer density centrifugation and visualized via epifluorescence microscopy (FM) and scanning electron microscopy (SEM). Total cell-carbon was calculated from amino acid-carbon, which was analyzed by high-performance liquid chromatography (HPLC) after cells had been purified by fluorescence-activated cell sorting (FACS). The majority of microbial cells in the sediment have coccoid or slightly elongated morphology. From the sediment surface to the deepest investigated sample (~60 m below the seafloor), the cell volume of both coccoid and elongated cells decreased by an order of magnitude from ~0.05 to 0.005 μm3. The cell-specific carbon content was 19–31 fg C cell−1, which is at the lower end of previous estimates that were used for global estimates of microbial biomass. The cell-specific carbon density increased with sediment depth from about 200 to 1000 fg C μm−3, suggesting that cells decrease their water content and grow small cell sizes as adaptation to the long-term subsistence at very low energy availability in the deep biosphere. We present for the first time depth-related data on the cell volume and carbon content of sedimentary microbial cells buried down to 60 m below the seafloor. Our data enable estimates of volume- and biomass-specific cellular rates of energy metabolism in the deep biosphere and will improve global estimates of microbial biomass.